Mechanisms of extrahepatic vasodilation in portal hypertension. Issue 9 (29th April 2008) - Hennenberg, M; Trebicka, J; Sauerbruch, T; Heller, J
Abstract : In liver cirrhosis, abnormal persistent extrahepatic vasodilation leads to hyperdynamic circulatory dysfunction which essentially contributes to portal hypertension. Since portal hypertension is a major factor in the development of complications in cirrhosis, the mechanisms underlying this vasodilation are of paramount interest. Extensive studies performed in cirrhotic patients and animals revealed that this vasodilation is associated on the one hand with enhanced formation of vasodilators, and on the other hand with vascular hyporesponsiveness to vasoconstrictors. The latter phenomenon has been termed "vascular hypocontractility". It is caused by a combination of different mechanisms and factors described in this review.